Ügynökök és bennfentesek – A bennfentes kereskedelem és az ügynök–költség összefüggései - Kecskés, András (Debreceni Jogi Műhely, 2016)
This paper examines insider trading regulation regulations from the viewpoint of agency costs. An overview is given regarding the different definitions of insider trading in jurisprudence which helps establishing the essence of this behaviour. The author also aims to give an insight to the agency problem and agency costs which arise in a business organisation with separate ownership and management. Only through that can be the effects of insider trading demonstrated on agency costs. The article aims to give a balanced overview by enumerating reasons whether insider trading increases or decreases agency costs. If it raises agency costs then prohibition is justified. If it decreases agency costs, e.g. it serves as a more efficient compensation mechanism, then allowing insider trading might be more beneficial.